Mathematics Anxiety as a Learning Problem in Junior High School: A Systematic Review from Psychological and Pedagogical Perspectives - Dwijayanti, Agil; Suhardi; Kusno (Universitas Islam Negeri Raden Intan Lampung, 2026)
Mathematics anxiety remains a critical learning problem in junior high school because it affects students’ emotional readiness, cognitive processing, classroom participation, and mathematical achievement. This systematic literature review aims to synthesize recent evidence on mathematics anxiety as an integrated psychological and pedagogical issue in mathematics learning. Guided by PRISMA 2020, this study reviewed 18 publications selected from Scopus, ScienceDirect, and Google Scholar. The selected studies were analyzed through thematic synthesis using a structured extraction matrix and quality appraisal procedure. The findings reveal that mathematics anxiety is closely related to low self-efficacy, fragile motivation, weak self-regulated learning, limited emotional regulation, working memory interference, and negative prior learning experiences. These factors create a reinforcing cycle in which fear of failure reduces participation, weakens persistence, and limits students’ opportunities to develop mathematical understanding. The review also shows that pedagogical conditions, including rigid instruction, limited scaffolding, unsupportive feedback, assessment pressure, weak peer interaction, and unsafe classroom climates, may intensify anxiety. Conversely, formative assessment, differentiated instruction, peer support, gradual scaffolding, and psychologically safe communication can reduce anxiety and strengthen engagement. This study contributes by reframing mathematics anxiety as a systemic psychological-pedagogical learning barrier rather than an individual emotional weakness. The findings imply that mathematics instruction, particularly within the Merdeka Curriculum context, should integrate cognitive support, emotional safety, responsive feedback, and structured autonomy to help students learn mathematics with confidence and resilience more effectively and sustainably.